Implementation of Coupled Inductor Based 7-level Inverter with Reduced Switches - R. Palanisamy; K. Vijayakumar; Aishwarya Bagchi; Vachika Gupta; Swapnil Sinha (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
This paper proposes implementation of coupled inductor based 7 level inverter with reduced number switches. The inverter which generates the sinusoidal output voltage by the use of coupled inductor with reduced total harmonic distortion. The voltage stress on each switching devices, capacitor balancing and common mode voltage can be minimized. The proposed system which gives better controlled output current and improved output voltage with diminished THD value. The switching devices of the system are controlled by using hysteresis current control algorithm by comparing the carrier signals with constant pulses with enclosed hysteresis band value. The simulation and experimental results of the proposed system outputs are verified using matlab/Simulink and TMS320F3825 dsp controller respectively.